Effect of exercise on depression and fatigue in breast cancer women undergoing chemotherapy: A randomized controlled trial. Issue 7 (July 2021) - Mostafaei, Fatemeh; Azizi, Mohammad; Jalali, Amir; Salari, Nader; Abbasi, Parvin
Abstract: Background: Depression and fatigue are common consequences of breast cancer that lead to dysfunction and reduced quality of life of patients. The aim of the present study was to determine the effect of exercise program on depression and fatigue in breast cancer women undergoing chemotherapy. Methods: This randomized controlled trial study was performed on 60 breast cancer women undergoing chemotherapy in Kermanshah hospitals from 2017-2018. Participants were selected using convenience sampling and were randomly divided into intervention and control groups. Data collection tools included demographic information form and standard Beck depression inventory (BDI-II) and fatigue severity scale (FSS). The intervention group performed the 20-30-minute indoor exercise program 3 sessions a week for 6 weeks. Questionnaires were completed before, immediately, and one month after the intervention by both groups and data analysis was carried out using SPSS ver.22. Results: There was no statistically significant difference between the two groups in terms of the mean fatigue intensity and depression scores before the intervention; however, the mean fatigue intensity scores were significantly decreased in the intervention group as compared to the control group immediately and one month after the intervention (P = 0.001). There was no statistically significant difference between the two groups in terms of mean depression score immediately and one month after the intervention (p > 0.05). Conclusion: Considering that indoor exercises reduced fatigue in breast cancer women undergoing chemotherapy, patients are recommended to perform exercise interventions as a non-pharmacological, safe, easy, and non-invasive solution to improve their physiological capacities and functional abilities as well as Quality of life. On the other hand, since exercise program had no effect on depression among breast cancer women in the present study, longer studies with larger sample size are recommended. Abstract : Depression, Fatigue, Breast cancer, Exercise, Randomized controlled trial.